The Implementation of Discipline in Fostering a Sense of Responsibility in Children Aged 5–6 Years in Class K5B at Shining Kids School, Palangka Raya City - Selvia Veronika; Rina Teriasi; Lisa Maneli (EDUJAVARE: International Journal of Educational Research, 2026)
-